Addressing power imbalances in biosequestration governance. (25th April 2021) - Lovera‐Bilderbeek, Simone; Lahiri, Souparna
Abstract: Climate change is a global challenge that requires strong governance on a global scale. The Intergovernmental Panel on Climate Change has suggested that large‐scale biosequestration in the form of forest restoration or tree plantation establishment is a potential form of carbon dioxide removal (CDR) that could contribute significantly to climate change mitigation. Yet it has also cautioned that this approach has social and environmental trade‐offs that need to be addressed through enhanced land governance. Land governance, per definition, has a strong local dimension as most lands are inhabited by local communities. Glocal and other multi‐scale governance approaches have been proposed to address potential conflicts between global policies and the rights, needs and priorities of local communities. Yet these approaches often overlook the power imbalances between the actors that design global climate policies and the local, often politically and economically marginalized, indigenous and other forest‐dependent communities that are directly impacted by these policies. The paper will explore to what extent theoretical concepts like rights‐based approaches have been able to address these conflicts and power imbalances, and whether more profound changes in governance systems are required to ensure equitable implementation of CDR. Abstract : It is unlikely that imbalances in biosequestration governance can be addressed without a profound transformative change in overall earth system governance. This would include reversing the corporate capture of policy‐making through disconnecting financial dependencies and other interlinkages between public and private sector interests, and an overall financial and political strengthening of genuinely participatory, rights‐based public policy‐making structures.